Selective transduction of cerebellar Purkinje and granule neurons using delivery of AAV-PHP.eB and AAVrh10 vectors at axonal terminal locations - Surdyka, Magdalena; Jesion, Ewelina; Niewiadomska-Cimicka, Anna; Trottier, Yvon; Kalinowska-Pośka, Żaneta; Figiel, Maciej (Frontiers in Molecular Neuroscience, 2022)
Adeno-associated virus (AAV)-based brain gene therapies require precision without off-targeting of unaffected neurons to avoid side effects. The cerebellum and its cell populations, including granule and Purkinje cells, are vulnerable to neurodegeneration; hence, conditions to deliver the therapy to specific cell populations selectively remain challenging. We have investigated a system consisting of the AAV serotypes, targeted injections, and transduction modes (direct or retrograde) for targeted delivery of AAV to cerebellar cell populations. We selected the AAV-PHP.eB and AAVrh10 serotypes valued for their retrograde features, and we thoroughly examined their cerebellar transduction pattern when injected into lobules and deep cerebellar nuclei. We found that AAVrh10 is suitable for the transduction of neurons in the mode highly dependent on placing the virus at axonal terminals. The strategy secures selective transduction for granule cells. The AAV-PHP.eB can transduce Purkinje cells and is very selective for the cell type when injected into the DCN at axonal PC terminals. Therefore, both serotypes can be used in a retrograde mode for selective transduction of major neuronal types in the cerebellum. Moreover, our in vivo transduction strategies are suitable for pre-clinical protocol development for gene delivery to granule cells by AAVrh10 and Purkinje cells by AAV-PHPeB.